Implementasi IDS dan IPS terhadap Serangan TCP Port Scanning dan ICMP Flooding - Muhammad Koprawi; Razzanda, Iqbal Maqdum (The Indonesian Journal of Computer Science, 2024)
The implementation of Intrusion Detection System (IDS) and Intrusion Prevention System (IPS) is a crucial step in maintaining network security. This research aims to test the effectiveness of IDS and IPS in detecting and preventing TCP port scanning attacks and ICMP flooding attacks and also providing real-time notifications using Telegram. The methodology used includes configuring a test environment that reflects real network scenarios, where various attacks are initiated to test the IDS and IPS responses. The experimental results show that IDS is able to detect suspicious activity with a high degree of accuracy, while IPS is effective in blocking identified attacks, thereby reducing potential damage to the system. Proper implementation of IDS and IPS can significantly improve network security by early detecting and preventing cyberattacks.